Qualitative process study to explore the perceived burdens and benefits of a digital intervention for self-managing high blood pressure in Primary Care in the UK - Morton, K; Dennison, L; Bradbury, K; Band, R; May, C; Raftery, J; Little, P; McManus, R; Yardley, L (BMJ Publishing Group, 2018)
Objectives Digital interventions can change patients’ experiences of managing their health, either creating additional burden or improving their experience of healthcare. This qualitative study aimed to explore perceived burdens and benefits for patients using a digital self-management intervention for reducing high blood pressure. A secondary aim was to further our understanding of how best to capture burdens and benefits when evaluating health interventions. Design Inductive qualitative process study nested in a randomised controlled trial. Setting Primary Care in the UK. Participants 35 participants taking antihypertensive medication and with uncontrolled blood pressure at baseline participated in semistructured telephone interviews. Intervention Digital self-management intervention to support blood pressure self-monitoring and medication change when recommended by the healthcare professional. Analysis Data were analysed using inductive thematic analysis with techniques from grounded theory. Results Seven themes were developed which reflected perceived burdens and benefits of using the intervention, including worry about health, uncertainty about selfmonitoring and reassurance. The analysis showed how beliefs about their condition and treatment appeared to influence participants’ appraisal of the value of the intervention. This suggested that considering illness and treatment perceptions in Burden of Treatment theory could further our understanding of how individuals appraise the personal costs and benefits of self-managing their health. Conclusions Patients’ appraisal of the burden or benefit of using a complex self-management intervention seemed to be influenced by experiences within the intervention (such as perceived availability of support) and beliefs about their condition and treatment (such as perceived control and risk of side effects). Developing our ability to adequately capture these salient burdens and benefits for patients could help enhance evaluation of self-management interventions in the future. Many participants perceived important benefits from using the intervention, highlighting the need for theory to recognise that engaging in self-management can include positive as well as negative aspects.